Optimalisasi Identitas Visual melalui Media Sosial untuk Meningkatkan Strategi Digital Marketing UMKM: Studi Kasus Warung Ibu Marni - Adinda Putri Kamalia; Arif Hidayat Lubis; Farida Syah Damanik; Muhammad Hafizhan Fakhri; Hotmatua Paralihan (BADAN PENERBIT STIEPARI PRESS, 2025)
The development of digital technology encourages MSMEs to adapt through social media-based marketing strategies and strengthening their visual identity. This study aims to analyze the role of visual identity and social media as digital marketing instruments in MSME development, using a case study of Warung Ibu Marni in Simalungun. The method used is descriptive qualitative through interviews, observation, and documentation. The results show that a consistent visual identity strengthens brand image, while social media effectively expands promotion and interaction with consumers. The integration of the two increases business visibility, customer networks, and the sustainable growth of MSMEs. Thus, visual identity and social media are proven to be important strategies for MSMEs to increase competitiveness in the digital era and can serve as practical references for the development of similar businesses. Furthermore, this study also confirms that MSMEs that utilize uniform logo designs, packaging, and social media displays are able to build consumer trust. Social media functions not only as a promotional tool but also as a communication channel that allows for direct feedback from customers. This provides opportunities for MSMEs to innovate according to market needs. This implementation strategy also supports increasing digital literacy among small business owners to be more adaptive to changes in consumer behavior. Thus, the collaboration between visual branding aspects and digital platforms becomes a strong foundation for the sustainable growth of MSMEs.